Limelighting Plant Invasion in India Through The Gleanings of Bhela Samhita - Patil, Dinkarrao Amrutrao (Plantae Scientia, 2024)
Developing nations like India are struggling in present time to conserve and manage biodiversity in a sustainable manner. However, prior to this movement, we must have information regarding status and changing patterns of biodiversity. The present author is engaged revealing floral elements invaded in Indian subcontinent. At this background, the present is an attempt to limelight exotic plant diversity through the lens of ancient scripture viz., Bhela Samhita which is rich in Sanskrit plant names of medicinal significance. This Samhita informs about 286 medicinal plant species. Out of these, a total of 98 exotic species are revealed belonging to 89 genera and 49 families of angiosperms. The dicotyledonous species have fairly invaded in India as compared to the monocotyledons. Their habital categorization and status regarding wildness or cultigen is also revealed along with their nativities in the world. The sum total of evidences may be of utility in view of biodiversity management and its conservation in India.